Motivations for the Use of English on Customs Officers’ Work Performance (Journal of Organizational Psychology, 2019)
This case study qualitatively explores the intrinsic and extrinsic motivations of Costa Rican customs workers for their use of English in the workplace in order to identify ways that human resource development (HRD) managers can then develop and provide relevant, effective English training to employees able to meet the expectations of English-speaking arrivals. Results identified prior negative English learning experiences and little to no support in the workplace for English use as the most important (negative) intrinsic and extrinsic motivations, respectively, for English use by participants. Most importantly, it highlights an imperative to increase the intrinsic motivation of customs officers.
Keywords: Organizational Psychology; human resource development; English; Customs Officers; Costa Rica